An umpolung strategy for intermolecular [2 + 2 + 1] cycloaddition of aryl aldehydes and nitriles: a facile access to 2, 4, 5-trisubstituted oxazoles. Issue 27 (27th June 2022) - Basavaiah, Deevi; Golime, Gangadhararao; Banoth, Shivalal; Todeti, Saidulu
Abstract : An unprecedented intermolecular [2 + 2 + 1] cycloaddition strategy between two aryl aldehydes and a nitrile, wherein one of the aryl aldehydes serves as a carbanion (or equivalent) in the presence of TMSOTf for obtaining oxazole framework is presented. Abstract : We have described the first example of an umpolung strategy for intermolecular [2 + 2 + 1] cycloaddition between two aryl aldehydes and a nitrile under the influence of TMSOTf that proceeds through the formation of N–C, O–C and C–C bonds providing a simple synthetic protocol for obtaining 2, 4, 5-trisubstituted oxazoles.